2013
DOI: 10.1007/s12032-013-0595-7
|View full text |Cite|
|
Sign up to set email alerts
|

Notch3 overexpression associates with poor prognosis in human non-small-cell lung cancer

Abstract: Notch3 receptor is one of the mammalian Notch family receptors (Notch1-4) which plays an important role in the regulation of cellular proliferation, differentiation, and apoptosis. Overexpression of Notch3 is associated with tumorigenesis. In order to assess the expression of Notch3 in Chinese non-small-cell lung cancer (NSCLC) patients and determine its association with prognosis, we designed a prospective study with five years of follow-up to evaluate Notch3 expression in NSCLC tissues and adjacent non-cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 23 publications
3
55
0
Order By: Relevance
“…Almost all cases of T cell acute lymphoblastic leukemia (T-ALL), and colorectal, pancreatic and ovarian cancer have been reported to exhibit aberrant Notch 3 expression (6,8,16,17). Our previous study also reported that Notch 3 overexpression was associated with a poor prognosis in NSCLC patients (18). However, the prognostic role of Notch 3 compared with other Notch family members and its association with Notch 1 in human NSCLC remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…Almost all cases of T cell acute lymphoblastic leukemia (T-ALL), and colorectal, pancreatic and ovarian cancer have been reported to exhibit aberrant Notch 3 expression (6,8,16,17). Our previous study also reported that Notch 3 overexpression was associated with a poor prognosis in NSCLC patients (18). However, the prognostic role of Notch 3 compared with other Notch family members and its association with Notch 1 in human NSCLC remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…With respect to Notch3, Haruki et al (12) found that the positive expression rate was ~37% (32/87). However, Zhou et al (13) and Ye et al (14) identified that the level of Notch3 increased in NSCLC tissues. The deviations in the expression of Notch1 and Notch3 may be due to the heterogeneity of the lung cancer samples.…”
Section: Introductionmentioning
confidence: 99%
“…of LAC (9)(10)(11)(12)(13)(14). Therefore, the present study chose to analyze the expression of Notch1 and Notch3 proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al (68) detected Notch 3 receptor expression in different types of lung cancer, and they found that Notch 3 expression was high in lung squamous cell carcinoma and adenocarcinoma, but low in small cell carcinoma, compared with the corresponding non-tumor tissue. In addition, the Notch 3 receptor showed its potential ability of predicting the prognosis of patients with NSCLC (69). In this recent report, high levels of the Notch 3 receptor were detected in ~51.1% of cases and were associated with a short survival rate.…”
Section: Breast Cancermentioning
confidence: 87%